Preparation method of lithium iron phosphate material and lithium iron phosphate material
Through the multi-grade and secondary hybrid coating technology of precursors with different titanium element content, the compaction density of lithium iron phosphate materials is improved, the problem of short range of lithium iron phosphate batteries is solved, and the energy density of lithium ion batteries is improved and battery capacity.
Patent Information
- Application Number
- CN202411279118.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Lithium iron phosphate batteries have a low share in the power market, mainly due to their short range, which leads to a low powder compaction density of lithium iron phosphate materials and cannot fully utilize their potential energy density.
Through the precursor mixed sintering and secondary mixed coating technology with different titanium element content, the powder compaction density of lithium iron phosphate material is improved. The specific steps include primary mixed sintering and crushing, followed by addition of linking agent and secondary carbon source for two Sub-mix, drying and secondary sintering to form a high-pressure density lithium iron phosphate material.
The compaction density of lithium iron phosphate material has been improved to 2.58g/cm3 to 2.72g/cm3, which has improved the energy density and battery capacity of lithium-ion batteries and extended the battery range.
Smart Images

Figure CN119118092A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular, relates to a preparation method of a lithium iron phosphate material and the lithium iron phosphate material. Background Art
[0002] Green and environmentally friendly lithium-ion batteries are widely welcomed by consumers due to their suitable operating voltage, long cycle life, high energy density, low self-discharge and other advantages, and their application areas are constantly expanding. Among them, positive electrode materials are an important component of lithium-ion batteries, and lithium iron phosphate has attracted widespread attention due to its good cycle performance, high safety, low price, and environmental friendliness, becoming one of the most mainstream positive electrode materials for lithium-ion batteries on the market.
[0003] At present, the market share of lithium iron phosphate batteries in the power market is still not high, mainly due to the short driving range of lithium iron phosphate batteries. Therefore, researchers in this field focus on how to improve the volume energy density of lithium iron phosphate materials. An important direction for improving the volume energy density is to increase the powder compaction density of lithium iron phosphate materials. At present, the powder compaction density of more mature lithium iron phosphate products is 2.58g / cm 3 The theoretical powder compaction density of lithium iron phosphate material is 3.6g / cm 3 Therefore, the powder compaction density of lithium iron phosphate materials has a large room for improvement.
[0004] In view of this, the present invention is proposed. Summary of the invention The object of the present invention is to provide a method for preparing a lithium iron phosphate material and the lithium iron phosphate material. The method can prepare lithium iron phosphate materials with large and small gradations, which is beneficial to improving the compaction density of the lithium iron phosphate material.
[0005] In order to achieve the above object, the present invention provides a method for preparing a lithium iron phosphate material in a first aspect, comprising the following steps: (1) Precursors with different titanium content are mixed once, sintered once, and crushed once to obtain lithium iron phosphate; the precursors with different titanium content include a phosphorus source, an iron source, a lithium source, a primary carbon source, and a titanium source; (2) The lithium iron phosphate is added to a mixture of a connector and a secondary carbon source for secondary mixing, followed by drying, secondary sintering, and crushing to obtain a lithium iron phosphate material.
[0006] In some embodiments, the precursors with different titanium content include at least two of a first precursor, a second precursor, and a third precursor, wherein the content of the different titanium elements ranges from 500 ppm to 3500 ppm.
[0007] In some embodiments, the titanium content of the first precursor is [500ppm, 1500ppm]; the titanium content of the second precursor is [1500ppm, 2500ppm]; and the titanium content of the third precursor is (2500ppm, 3500ppm).
[0008] In some embodiments, the precursors with different titanium content include any two of the first precursor, the second precursor and the third precursor.
[0009] In some embodiments, the precursors with different titanium content include the first precursor, the second precursor and the third precursor.
[0010] In some embodiments, the mass ratio of the first precursor and the second precursor, or the first precursor and the third precursor, or the second precursor and the third precursor is [10%, 50%]: [50%, 90%]; Preferably, the mass ratio of the first precursor and the second precursor, or the first precursor and the third precursor, or the second precursor and the third precursor is [20%, 40%]: [60%, 80%].
[0011] In some embodiments, the mass ratio of the first precursor, the second precursor and the third precursor is (0%, 30%]: [50%, 90%]: (0%, 30%]; Preferably, the mass ratio of the first precursor, the second precursor and the third precursor is [5%, 15%]: [70%, 80%]: [5%, 15%].
[0012] In some embodiments, the linker is a titanate coupling agent; and / or the secondary carbon source is a hydroxyl-containing carbon source.
[0013] In some embodiments, the mass ratio of the linker to the secondary carbon source is 1:[1,3]; and / or the mass ratio of the linker to the lithium iron phosphate is 1:[80,100].
[0014] In a second aspect, the present invention provides a lithium iron phosphate material, wherein the lithium iron phosphate material is prepared by the preparation method of the lithium iron phosphate material of any of the above embodiments, and the compaction density of the lithium iron phosphate material powder is [2.58g / cm 3 ,2.72 g / cm 3 ].
[0015] The preparation method of the lithium iron phosphate material provided by the present invention mixes precursors with different titanium content in different proportions in a primary mixing process to obtain lithium iron phosphate with large and small gradations, thereby improving the compaction density of the lithium iron phosphate. At the same time, in a secondary mixing process, a connector and a secondary carbon source are used to jointly coat the lithium iron phosphate, thereby further improving the compaction density of the lithium iron phosphate material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 Schematic diagram of the compaction effect of powder particles with different gradations; Figure 2 The particle size curve of the lithium iron phosphate material prepared in Example 1; Figure 3 The particle size curve of the lithium iron phosphate material prepared in Example 2; Figure 4 The particle size curve of the lithium iron phosphate material prepared in Example 3; Figure 5 The particle size curve of the lithium iron phosphate material prepared in Comparative Example 1; Figure 6 The particle size curve of the lithium iron phosphate material prepared in Comparative Example 2; Figure 7 This is the SEM image of the lithium iron phosphate material prepared in Example 1. DETAILED DESCRIPTION
[0018] Hereinafter, the method for preparing the lithium iron phosphate material of the present invention, the specific embodiments of the lithium iron phosphate material and the lithium ion battery will be described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0019] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. In particular, "()", ")", "[" and "]" represent intervals, where "(" or ")" represents an open interval, that is, the endpoint values of the interval are not included; "[" and "]" represent a closed interval, that is, the endpoints within the interval are included. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.
[0020] Specifically, for example, if a range of 60-120 and 80-110 is listed for a particular parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been fully listed in this article, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a certain parameter is expressed as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. If (10, 20) is listed, it is understood as any value between 10 and 20, excluding 10 and 20; (10, 20] is understood as any value between 10 and 20, excluding 10 but including 20.
[0021] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0022] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0023] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0024] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0025] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0026] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate material, comprising the following steps: (1) Precursors with different titanium content are mixed once, sintered once, and crushed once to obtain lithium iron phosphate; the precursors with different titanium content include a phosphorus source, an iron source, a lithium source, a primary carbon source, and a titanium source; (2) The lithium iron phosphate is added to a mixture of a connector and a secondary carbon source for secondary mixing, followed by drying, secondary sintering, and crushing to obtain a lithium iron phosphate material.
[0027] In some embodiments, the precursors with different titanium content are obtained by adding a phosphorus source, an iron source, a lithium source, a primary carbon source and a titanium source into deionized water, grinding the mixture to a certain particle size to obtain a slurry, and then spray drying the mixture once.
[0028] In some embodiments, the iron source is at least one of ferric phosphate, ferrous oxide and ferrous oxalate; the phosphorus source is at least one of ferric phosphate, ammonium dihydrogen phosphate and phosphoric acid; the lithium source is at least one of lithium carbonate, lithium hydroxide and lithium dihydrogen phosphate; and the primary carbon source is at least one of glucose, sucrose, polyethylene glycol-1000, polyethylene glycol-1500, polyethylene glycol-2000, polyethylene glycol-4000, polyethylene glycol-6000, polyethylene glycol-10000, citric acid, cyclodextrin and polyvinyl alcohol.
[0029] In some embodiments, the molar ratio of phosphorus, iron and lithium in the precursor is [1, 1.2]: 1: [1, 1.2], and the mass fraction of the primary carbon source in the precursor is [2.5%, 6%].
[0030] In some embodiments, the titanium source is at least one of rutile phase nano-titanium dioxide, anatase phase nano-titanium dioxide, brookite phase nano-titanium dioxide, tetrabutyl titanate, titanium boride, titanium sulfate, titanate coupling agent, titanyl sulfate and titanium citrate.
[0031] In some embodiments, precursors with different titanium content are mixed once, sintered once, and crushed once to obtain lithium iron phosphate. After titanium is doped into the lithium iron phosphate lattice, the grain size is refined. Different doping amounts have different degrees of size refinement. Precursors with different titanium content are sintered to produce lithium iron phosphate with different particle size ranges. Mixing lithium iron phosphate with different particle size ranges can increase the compaction density of lithium iron phosphate. Lithium iron phosphate with high compaction density can increase the energy density of lithium-ion batteries.
[0032] In some embodiments, the precursor is at least two of the titanium content of 500ppm to 3500ppm. In the present invention, the titanium content is selected within this content range. The precursor with too low titanium content forms larger lithium iron phosphate particles after sintering, so that the compaction density is low. The precursor with too high titanium content forms smaller lithium iron phosphate particles after sintering, and the compaction density is low.
[0033] In some embodiments, a precursor having a titanium content of [500ppm, 1500ppm] is a first precursor; a precursor having a titanium content of [1500ppm, 2500ppm] is a second precursor; and a precursor having a titanium content of (2500ppm, 3500ppm] is a third precursor. The precursors having different titanium content include at least two of the first precursor, the second precursor and the third precursor.
[0034] In some embodiments, two precursors with different titanium content are mixed at one time, and the precursors with different titanium content include any two of the first precursor, the second precursor, and the third precursor.
[0035] In some embodiments, three precursors with different titanium content are mixed at one time, and the precursors with different titanium content include the first precursor, the second precursor, and the third precursor.
[0036] The lithium iron phosphate obtained by sintering two or more precursors with different titanium content levels has a graded effect of two or more levels, and the obtained lithium iron phosphate material has a higher compaction density. Figure 1 It can be seen that compared with the two-level gradation, the three-level gradation has higher space utilization efficiency and a corresponding larger stacking density.
[0037] In some embodiments, when two precursors with different titanium content are mixed at one time, the mass ratio of the first precursor and the second precursor, or the first precursor and the third precursor, or the second precursor and the third precursor is [10%, 50%]: [50%, 90%]. The mass ratio of the precursor with a lower titanium content is lower, and the mass ratio of the precursor with a higher titanium content is higher, which is beneficial to both improve the compaction density of lithium iron phosphate powder and the corresponding lithium ion battery capacity.
[0038] In some embodiments, the mass ratio of the first precursor and the second precursor, or the first precursor and the third precursor, or the second precursor and the third precursor is [20%, 40%]: [60%, 80%].
[0039] In some embodiments, the particle size distribution diagram of the lithium iron phosphate material prepared by mixing the first precursor and the second precursor, or the first precursor and the third precursor, or the second precursor and the third precursor in different mass ratios shows a bimodal particle size distribution, with the first peak particle size range of 0.1-1.5 μm and the second peak particle size range of 1.5-15.0 μm.
[0040] In some embodiments, when three precursors with different titanium content are mixed at one time, the mass ratio of the first precursor, the second precursor and the third precursor is (0%, 30%]: [50%, 90%]: (0%, 30%]. The mass proportion of the second precursor is relatively large, and the mass proportion of the first precursor and the third precursor is relatively small, which is beneficial to taking into account both improving the compaction density of lithium iron phosphate powder and the corresponding lithium-ion battery capacity.
[0041] In some embodiments, the mass ratio of the first precursor, the second precursor and the third precursor is [5%, 15%]: [70%, 80%]: [5%, 15%].
[0042] In some embodiments, the particle size distribution diagram of the lithium iron phosphate material prepared by mixing the first precursor, the second precursor and the third precursor in different mass proportions shows three peaks, the first peak particle size range is 0.1-1.0 μm, the second peak particle size range is 1.0-8.0 μm, and the third peak particle size range is 8.0-30.0 μm.
[0043] In some embodiments, the linker and the secondary carbon source are mixed in water, and then the lithium iron phosphate is added and mixed again, followed by secondary spray drying, secondary sintering, and crushing to obtain the lithium iron phosphate material.
[0044] In some embodiments, the linking agent is a titanate coupling agent.
[0045] In some embodiments, the secondary carbon source is a hydroxyl-containing carbon source, such as polyethylene glycol-1500, polyethylene glycol-2000, polyethylene glycol-4000, polyethylene glycol-6000, polyethylene glycol-10000, phenol, and the like.
[0046] The connector plays a role of "connecting bridge". The connector has polar and non-polar groups. The non-polar groups are adsorbed on the weak polar surface of lithium iron phosphate, and the polar groups are combined with hydroxyl groups in the hydroxyl-containing carbon source, thereby improving the compatibility of the hydroxyl-containing carbon source with lithium iron phosphate, thereby improving the coating thickness and coating uniformity of the hydroxyl-containing carbon source on the surface of lithium iron phosphate. At the same time, due to the coating of the hydroxyl-containing carbon source, the dispersibility of lithium iron phosphate is improved, thereby avoiding agglomeration. In the present invention, through the coordinated use of the connector and the hydroxyl-containing carbon source, the lithium iron phosphate material after secondary sintering has a uniform carbon coating layer.
[0047] The connecting agent used in the present invention is a titanium-containing coupling agent, mainly because titanium is a "beneficial factor" in lithium iron phosphate. If other coupling agents are used, impurities will be introduced, reducing the stability of the lithium iron phosphate material.
[0048] In some embodiments, the mass ratio of the linker to the secondary carbon source is 1:[1,3].
[0049] In some embodiments, the mass ratio of the linker to the lithium iron phosphate is 1:[80,200].
[0050] In some embodiments, the mass ratio of the mixture of the linker and the secondary carbon source to water is 1:[30,50].
[0051] In some embodiments, the primary sintering and secondary sintering temperatures are independently [780° C., 850° C.] Preferably, the primary sintering and secondary sintering temperatures are independently [800° C., 820° C.].
[0052] In some embodiments, the present invention further provides a lithium iron phosphate material, wherein the mass fraction of carbon in the lithium iron phosphate material obtained by the preparation method provided by the present invention is [1.10%, 1.50%]. Preferably, the mass fraction of carbon in the lithium iron phosphate material is [1.15%, 1.30%].
[0053] In some embodiments, the titanium doping amount of the lithium iron phosphate material is [1000 ppm, 5000 ppm].
[0054] In some embodiments, the powder compaction density of the lithium iron phosphate material is [2.58 g / cm 3 ,2.72 g / cm 3 ].
[0055] In some embodiments, a lithium ion battery is prepared using the lithium iron phosphate material prepared by the present invention, and within the voltage range of [2.0V, 3.75V], the 0.1C charge specific capacity range is: [162.0 mAh / g, 164.5 mAh / g].
[0056] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0057] Example 1 (1) Preparation of precursors with different titanium contents: Preparation of the first precursor: 4.5 kg of glucose and 4.5 kg of polyethylene glycol (molecular weight of 1500) were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano titanium dioxide in the premix was 1000 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for 5 coarse grinding, and then sand-milled in a fine grinding sand mill to a particle size D50 of 0.60 ± 0.01 μm, and then spray-dried once to obtain the first precursor. The rate of the spray drying was 80 kg / h, the inlet temperature of the spray drying was 220°C, and the outlet temperature was 105°C.
[0058] Preparation of the second precursor: The only difference from the preparation of the first precursor is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 2000ppm.
[0059] Preparation of the third precursor: The only difference from the preparation of the first precursor is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 3000ppm.
[0060] (2) Precursors with different proportions of titanium content are mixed once to prepare lithium iron phosphate: The first precursor, the second precursor and the third precursor are mixed evenly in a high-speed mixer at a mass ratio of 10%:80%:10%, and the mixed precursors are placed in a graphite sagger, sintered at a constant temperature of 800°C in a roller kiln in a nitrogen atmosphere for 10 hours, and then cooled, crushed and demagnetized to obtain lithium iron phosphate.
[0061] (3) Preparation of lithium iron phosphate material: 1.0kg of isopropyl tri(dioctylphosphoyl)titanate and 2kg of polyethylene glycol (molecular weight 1500) were added to 150kg of deionized water for mixing, and then 100kg of the above-mentioned lithium iron phosphate was added for secondary mixing. The secondary mixture was sand-milled to a particle size D50 of 1.00±0.05um, and a lithium iron phosphate material intermediate was obtained by secondary spray drying. The secondary spray drying feed rate was 80kg / h, the inlet air temperature was 220°C, and the outlet air temperature was 105°C. The above-mentioned lithium iron phosphate material intermediate was placed in a graphite sagger, and sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at a temperature of 820°C, and then cooled, crushed and demagnetized to obtain the lithium iron phosphate material.
[0062] Embodiment 2: (1) Preparation of precursors with different titanium contents: Preparation of the first precursor: 4.5 kg of glucose and 4.5 kg of polyethylene glycol (molecular weight of 1500) were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano titanium dioxide in the premix was 1000 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for 5 coarse grinding, and then sand-milled in a fine grinding sand mill to a particle size D50 of 0.60 ± 0.01 μm, and then spray-dried once to obtain the first precursor. The rate of the spray drying was 80 kg / h, the inlet temperature of the spray drying was 220°C, and the outlet temperature was 105°C.
[0063] Preparation of the second precursor: The only difference from the preparation of the first precursor is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 2200ppm.
[0064] (2) Precursors with different proportions of titanium content are mixed once to prepare lithium iron phosphate: The first precursor and the second precursor are mixed evenly in a high-speed mixer at a mass ratio of 20%:80%, and then the mixed precursors are placed in a graphite sagger, sintered at a constant temperature of 800°C in a roller kiln in a nitrogen atmosphere for 10 hours, and then cooled, crushed and demagnetized to obtain lithium iron phosphate.
[0065] (3) Preparation of lithium iron phosphate material: 1kg of isopropyl tri(dioctylphosphoyl)titanate and 2kg of polyethylene glycol (molecular weight 1500) were added to 150kg of deionized water for mixing, and then 100kg of the above-mentioned lithium iron phosphate was added for secondary mixing. The secondary mixture was sand-milled to a particle size D50 of 1.00±0.05um, and a lithium iron phosphate material intermediate was obtained by secondary spray drying. The secondary spray drying feed rate was 80kg / h, the inlet air temperature was 220°C, and the outlet air temperature was 105°C. The above-mentioned lithium iron phosphate material intermediate was placed in a graphite sagger, and sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at a temperature of 820°C, and then cooled, crushed and demagnetized to obtain the lithium iron phosphate material.
[0066] Embodiment 3: The only difference between this embodiment and embodiment 2 is that the mass ratio of the first precursor to the second precursor in step (2) is replaced from 20%:80% to 40%:60%, and the other conditions and parameters are exactly the same as those in embodiment 2.
[0067] Embodiment 4: (1) Preparation of precursors with different titanium contents: Preparation of the first precursor: 4.5 kg of glucose and 4.5 kg of polyethylene glycol (molecular weight of 1500) were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano titanium dioxide in the premix was 500 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for 5 coarse grinding, and then sand-milled in a fine grinding sand mill to a particle size D50 of 0.60 ± 0.01 μm, and then spray-dried once to obtain the first precursor. The rate of the spray drying was 80 kg / h, the inlet temperature of the spray drying was 220°C, and the outlet temperature was 105°C.
[0068] Preparation of the second precursor: The only difference from the preparation of the first precursor is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 2500ppm.
[0069] Preparation of the third precursor: The only difference from the preparation of the first precursor is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 2600ppm.
[0070] (2) Precursors with different proportions of titanium content are mixed once to prepare lithium iron phosphate: The first precursor, the second precursor and the third precursor are mixed evenly in a high-speed mixer at a mass ratio of 15%:70%:15%, and the mixed precursors are placed in a graphite sagger, sintered at a constant temperature of 800°C in a roller kiln in a nitrogen atmosphere for 10 hours, and then cooled, crushed and demagnetized to obtain lithium iron phosphate.
[0071] (3) Preparation of lithium iron phosphate material: 1kg of isopropyl trioleyl titanate and 1kg of polyethylene glycol (molecular weight 1500) were added to 100kg of deionized water for mixing, and then 80kg of the above-mentioned lithium iron phosphate was added for secondary mixing. The secondary mixture was sand-milled to a particle size D50 of 1.00±0.05um, and a lithium iron phosphate material intermediate was obtained by secondary spray drying. The secondary spray drying feed rate was 80kg / h, the inlet air temperature was 220°C, and the outlet air temperature was 105°C. The above-mentioned lithium iron phosphate material intermediate was placed in a graphite sagger, and sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at a temperature of 820°C, and then cooled, crushed and demagnetized to obtain the lithium iron phosphate material.
[0072] Embodiment 5: (1) Preparation of precursors with different titanium contents: Preparation of the second precursor: 4.5 kg of glucose and 4.5 kg of polyethylene glycol (molecular weight of 1500) were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano titanium dioxide in the premix was 1500 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for 5 coarse grinding, and then sand-milled in a fine grinding sand mill to a particle size D50 of 0.60 ± 0.01 μm, and then spray-dried once to obtain the second precursor. The rate of the spray drying was 80 kg / h, the inlet temperature of the spray drying was 220°C, and the outlet temperature was 105°C.
[0073] Preparation of the third precursor: The only difference from the preparation of the second precursor is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 2600ppm.
[0074] (2) Precursors with different proportions of titanium content are mixed once to prepare lithium iron phosphate: The second precursor and the third precursor are mixed evenly in a high-speed mixer at a mass ratio of 20%:80%, and the mixed precursors are placed in a graphite sagger, sintered at a constant temperature of 800°C in a roller kiln in a nitrogen atmosphere for 10 hours, and then cooled, crushed and demagnetized to obtain lithium iron phosphate.
[0075] (3) Preparation of lithium iron phosphate material: 1kg of isopropyl tri(dioctylphosphoyl)titanate and 3kg of polyethylene glycol (molecular weight 1500) were added to 120kg of deionized water for mixing, and then 200kg of the above-mentioned lithium iron phosphate was added for secondary mixing. The secondary mixture was sand-milled to a particle size D50 of 1.00±0.05um, and a lithium iron phosphate material intermediate was obtained by secondary spray drying. The secondary spray drying feed rate was 80kg / h, the inlet air temperature was 220°C, and the outlet air temperature was 105°C. The above-mentioned lithium iron phosphate material intermediate was placed in a graphite sagger, and sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at a temperature of 820°C, and then cooled, crushed and demagnetized to obtain the lithium iron phosphate material.
[0076] Embodiment 6: (1) Preparation of precursors with different titanium contents: Preparation of the first precursor: 4.5 kg of glucose and 4.5 kg of polyethylene glycol (molecular weight of 1500) were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano titanium dioxide in the premix was 1400 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for 5 coarse grinding, and then sand-milled in a fine grinding sand mill to a particle size D50 of 0.60 ± 0.01 μm, and then spray-dried once to obtain the first precursor. The rate of the spray drying was 80 kg / h, the inlet temperature of the spray drying was 220°C, and the outlet temperature was 105°C.
[0077] Preparation of the third precursor: The only difference from the preparation of the first precursor is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 3500ppm.
[0078] (2) Precursors with different proportions of titanium content are mixed once to prepare lithium iron phosphate: The first precursor and the third precursor are mixed evenly in a high-speed mixer at a mass ratio of 20%:80%, and the mixed precursors are placed in a graphite sagger, sintered at a constant temperature of 800°C in a roller kiln in a nitrogen atmosphere for 10 hours, and then cooled, crushed and demagnetized to obtain lithium iron phosphate.
[0079] (3) Preparation of lithium iron phosphate material: 1kg of isopropyl tri(dioctylphosphoyl)titanate and 2kg of polyethylene glycol (molecular weight 1500) were added to 150kg of deionized water for mixing, and then 100kg of the above-mentioned lithium iron phosphate was added for secondary mixing. The secondary mixture was sand-milled to a particle size D50 of 1.00±0.05um, and a lithium iron phosphate material intermediate was obtained by secondary spray drying. The secondary spray drying feed rate was 80kg / h, the inlet air temperature was 220°C, and the outlet air temperature was 105°C. The above-mentioned lithium iron phosphate material intermediate was placed in a graphite sagger, and sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at a temperature of 820°C, and then cooled, crushed and demagnetized to obtain the lithium iron phosphate material.
[0080] Comparative Example 1: (1) Preparation of a titanium source-containing precursor: 4.5 kg of glucose and 4.5 kg of polyethylene glycol (molecular weight of 1500) were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano titanium dioxide in the premix was 2000 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for coarse grinding 5 times, and then sand-milled in a fine grinding sand mill to a particle size D50 of 0.60 ± 0.01 μm, and then ethanol spray-dried to obtain a precursor containing a titanium source, wherein the rate of the first spray drying was 80 kg / h, the inlet air temperature of the first spray drying was 220°C, and the outlet air temperature was 105°C.
[0081] (2) Preparation of lithium iron phosphate: The titanium source-containing precursor is placed in a graphite sagger, sintered at a constant temperature of 800° C. in a roller kiln in a nitrogen atmosphere for 10 hours, and then cooled, crushed and demagnetized to obtain lithium iron phosphate.
[0082] (3) Preparation of lithium iron phosphate material: 1.0kg of isopropyl tri(dioctylphosphoyl)titanate and 2kg of polyethylene glycol (molecular weight 1500) were added to 150kg of deionized water and mixed, and then the above-mentioned lithium iron phosphate was added for secondary mixing. The secondary mixture was sand-milled to a particle size D50 of 1.00±0.05um, and a lithium iron phosphate material intermediate was obtained by secondary spray drying. The secondary spray drying feed rate was 80kg / h, the inlet air temperature was 220°C, and the outlet air temperature was 105°C. The above-mentioned lithium iron phosphate material intermediate was placed in a graphite sagger, and sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at a temperature of 820°C, and then cooled, crushed and demagnetized to obtain the lithium iron phosphate material.
[0083] Comparative Example 2: The difference between this comparative example and comparative example 1 is that in step (3), "1.0 kg of isopropyl tri(dioctylphosphoyl)titanate and 2 kg of polyethylene glycol (molecular weight 1500) are added to 150 kg of deionized water and mixed" is replaced by "2 kg of polyethylene glycol (molecular weight 1500) is added to 150 kg of deionized water and mixed", and the other conditions and parameters are exactly the same as those in comparative example 1.
[0084] Comparative Example 3: (1) Preparation of a titanium source-containing precursor: 4.5 kg of glucose, 6.5 kg of polyethylene glycol (molecular weight of 1500) and 1.0 kg of isopropyl tri(dioctylphosphoyl) titanate were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano titanium dioxide in the premix was 2000 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for 5 coarse grinding, and then sand-milled in a fine sand mill to a particle size D50 of 0.60±0.01 μm, and then spray-dried once to obtain a precursor containing a titanium source, wherein the rate of the spray drying once was 80 kg / h, the inlet air temperature of the spray drying once was 220° C., and the outlet air temperature was 105° C.
[0085] (2) Preparation of lithium iron phosphate material: The titanium source-containing precursor is placed in a graphite sagger, sintered at a constant temperature of 820° C. in a roller kiln in a nitrogen atmosphere for 10 hours, and then cooled, crushed and demagnetized to obtain a lithium iron phosphate material.
[0086] Comparative Example 4: The difference between this comparative example and Example 1 is that in step (1), 90 kg of iron phosphate and rutile nano-titanium dioxide in the preparation of the first precursor are replaced by an equal amount of rutile nano-titanium dioxide and 90 kg of iron phosphate to obtain titanium-doped iron phosphate; 90 kg of iron phosphate and rutile nano-titanium dioxide in the preparation of the second precursor are replaced by an equal amount of rutile nano-titanium dioxide and 90 kg of iron phosphate to obtain titanium-doped iron phosphate; 90 kg of iron phosphate and rutile nano-titanium dioxide in the preparation of the third precursor are replaced by an equal amount of rutile nano-titanium dioxide and 90 kg of iron phosphate to obtain titanium-doped iron phosphate. Other conditions and parameters are exactly the same as those in Example 1.
[0087] Comparative Example 5: (1) Preparation of slurries with different titanium content: Preparation of the first slurry: 4.5 kg of glucose and 4.5 kg of polyethylene glycol (molecular weight 1500) were added to 230 kg of deionized water for dissolution, and then 90 kg of iron phosphate, 22.6 kg of lithium carbonate and rutile phase nano-titanium dioxide were added in sequence for premixing, wherein the proportion of titanium element in rutile phase nano-titanium dioxide in the premix was 1000 ppm. The premix was obtained after premixing for 1.5 hours, and the premix was placed in a coarse grinder for coarse grinding 5 times, and then sand-milled in a fine sand mill to a particle size D50 of 0.60 ± 0.01 μm to obtain the first slurry.
[0088] Preparation of the second slurry: The only difference from the preparation of the first slurry is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 2000ppm.
[0089] Preparation of the third slurry: The only difference from the preparation of the first slurry is that the proportion of titanium element in rutile phase nano-titanium dioxide in the premix is 3000ppm.
[0090] (2) After mixing slurries with different proportions of titanium content, lithium iron phosphate is prepared: The first slurry, the second slurry and the third slurry are mixed in a mass ratio of 10%:80%:10%, and then spray-dried to obtain a precursor, the spray drying rate is 80kg / h, the inlet air temperature of the spray drying is 220°C, and the outlet air temperature is 105°C. The mixed precursor is then placed in a graphite sagger, sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at 800°C, and then cooled, crushed and demagnetized to obtain lithium iron phosphate.
[0091] (3) Preparation of lithium iron phosphate material: 1.0kg of isopropyl tri(dioctylphosphoyl)titanate and 2kg of polyethylene glycol (molecular weight 1500) were added to 150kg of deionized water for mixing, and then 100kg of the above-mentioned lithium iron phosphate was added for secondary mixing. The secondary mixture was sand-milled to a particle size D50 of 1.00±0.05um, and a lithium iron phosphate material intermediate was obtained by secondary spray drying. The secondary spray drying feed rate was 80kg / h, the inlet air temperature was 220°C, and the outlet air temperature was 105°C. The above-mentioned lithium iron phosphate material intermediate was placed in a graphite sagger, and sintered at a constant temperature for 10 hours in a roller kiln in a nitrogen atmosphere at a temperature of 820°C, and then cooled, crushed and demagnetized to obtain the lithium iron phosphate material.
[0092] Effect example 1: In order to verify the performance of the lithium iron phosphate material of the present invention, the lithium iron phosphate material powders prepared in each embodiment and comparative example are tested for compaction density using instruments and methods known in the art. For example, the test may be performed with an electronic pressure testing machine with reference to GB / T 24533-2009 powder compaction density determination method, and the test powder weight is 1.0±0.05g and the test pressure is 3T.
[0093] The test results are shown in Table 1.
[0094] Effect Example 2: In order to verify the performance of the lithium iron phosphate material of the present invention, the lithium iron phosphate material prepared in each embodiment and comparative example was made into a button battery, and the preparation method was as follows: The lithium iron phosphate material is mixed evenly with conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone by a high-speed mixer, wherein the mass ratio of the lithium iron phosphate material, the conductive carbon black and the polyvinylidene fluoride is 90:5:5, and then coated on the aluminum foil by an automatic coating machine, and the coated aluminum foil is dried in an oven and cut into small discs of a required size, and weighed to obtain a positive electrode sheet; a pure lithium sheet is used as a negative electrode sheet, and a positive electrode shell, a negative electrode shell, a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte are assembled into a button battery as required.
[0095] The obtained button battery was placed on a battery testing system and allowed to stand for a period of time. The charge and discharge specific capacities at 0.1C and 1C were tested within a voltage range of [2.0V, 3.75V]. The test results are shown in Table 1.
[0096] Table 1
[0097] It can be seen from the results in Table 1 that, compared with the two-level grading schemes adopted in Examples 2 and 3, on the one hand, the three-level grading scheme adopted in Example 1 has both large particles, medium particles and small particles, high space utilization, and good stacking effect, so that the lithium iron phosphate material has a higher compaction density; at the same time, the lithium iron phosphate material obtained by the three-level grading scheme in Example 1 enables the lithium-ion battery to have a higher discharge specific capacity at 1C.
[0098] Compared with Comparative Example 1, the preparation method of the lithium iron phosphate material provided by the present invention, on the one hand, enables the lithium iron phosphate material to have a second / third level particle size distribution characteristic, enables the lithium iron phosphate material to have a high compaction characteristic of a second / third level grading, and at the same time enables the lithium ion battery to have a higher discharge specific capacity at 1C.
[0099] Compared with Comparative Example 2, in Comparative Example 1, isopropyl tri(dioctylphosphoyl) titanate coupling agent is used in the carbon coating process of lithium iron phosphate, which can make the polyethylene glycol more evenly coated on the surface of lithium iron phosphate, forming a uniform carbon coating layer after calcination, increasing the surface smoothness and sphericity of the lithium iron phosphate material, and making the lithium iron phosphate material have a higher compaction density.
[0100] Compared with Comparative Example 3, in Comparative Example 1, isopropyl tri(dioctylphosphoyloxy)titanate and polyethylene glycol are used to coat the surface of the prepared lithium iron phosphate, and the linker and the hydroxyl-containing carbon source form a uniform carbon coating layer after calcination. On the one hand, the uniform carbon coating layer increases the surface smoothness and sphericity of the lithium iron phosphate material, and the lithium iron phosphate material has a higher compaction density; on the other hand, the uniform carbon coating layer helps to improve the electronic conduction rate of the lithium ion battery.
[0101] Compared with comparative example 4, which uses titanium-doped iron phosphate as a raw material, the preparation method provided by the present invention uses a titanium source independently as a raw material. On the one hand, the titanium source is independently used as a raw material. By incorporating the lithium iron phosphate lattice during the synthesis process and regulating the growth of lithium iron phosphate, the effect of refining the lithium iron phosphate grains can be achieved. By controlling the particle size, the effect of particle size grading is achieved, so that the space utilization rate is high and the stacking effect is good. In comparative example 4, titanium-doped iron phosphate is directly used as a raw material. Since the unit cell volume shrinks after titanium doping, it affects the entry of subsequent Li ions, resulting in uneven lithium distribution in the lithium iron phosphate material, which ultimately affects the electrochemical properties of the material; at the same time, the effect on iron phosphate with a large amount of titanium doping is more significant, and the effect on iron phosphate with a small amount of titanium doping is smaller, so the lithium iron phosphate particles are smaller and larger, which affects the grading effect and reduces the compaction density of the lithium iron phosphate material.
[0102] Compared with Comparative Example 5 in which slurries with different contents of titanium sources are mixed in a certain proportion, the present invention provides a method for preparing lithium iron phosphate materials, in which slurries with different titanium content are spray-dried to obtain precursors with different titanium content, which are mixed in a certain proportion and then spray-dried for a second time to obtain lithium iron phosphate material intermediates with different titanium content, and lithium iron phosphate materials with different titanium doping amounts can be obtained by sintering; however, if the slurries are directly mixed and then sprayed, lithium iron phosphate materials doped with different titanium contents cannot be obtained, i.e., there is no multi-stage grading effect. Effect example 3: In order to verify the particle size distribution of the lithium iron phosphate material of the present invention, the lithium iron phosphate material samples prepared in each embodiment and comparative example were measured, and the key steps of the test were as follows: solvent addition: 20 ml of deionized water, shading degree: 8-12%.
[0103] Figure 2-Figure 6 The particle size distribution curves of the lithium iron phosphate materials prepared in various embodiments and comparative examples are shown in FIG.
[0104] Figure 2 The lithium iron phosphate material prepared in Example 1 has a three-peak particle size distribution curve, with the first peak particle size of 0.3-0.5 μm, the second peak particle size of 2-4 μm, and the third peak particle size of 15.0-25.0 μm.
[0105] Figure 3 This is the lithium iron phosphate material prepared in Example 2. It can be seen from the figure that the particle size distribution curve is a double-peak curve, the first peak particle size is 0.3-0.5 μm, and the second peak particle size is 2-5 μm.
[0106] Figure 4 The lithium iron phosphate material prepared in Example 3 has a double-peaked particle size distribution curve, with a first peak particle size of 0.4-0.6 μm and a second peak particle size of 2.0-4.0 μm.
[0107] Figure 5 This is the lithium iron phosphate material prepared by Comparative Example 1. It can be seen from the figure that the particle size distribution curve is a single-peak curve, and the single-peak particle size is 1.0-2.0 μm.
[0108] Figure 6 This is the lithium iron phosphate material prepared by Comparative Example 2. It can be seen from the figure that the particle size distribution curve is a single-peak curve, and the single-peak particle size is 2.0-4.0 μm.
[0109] Effect example 4: The morphology of the lithium iron phosphate material sample in Example 1 was observed using a scanning electron microscope.
[0110] Figure 7 This is the SEM image of the lithium iron phosphate material obtained in Example 1. Figure 7 It can be seen that the lithium iron phosphate material after three-level grading has large particles, medium particles and small particles, with high space utilization and good stacking effect.
[0111] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a lithium iron phosphate material, characterized in that: The following steps are involved: (1) Precursors with different titanium content are mixed once, sintered once, and crushed once to obtain lithium iron phosphate; the precursors with different titanium content include a phosphorus source, an iron source, a lithium source, a primary carbon source, and a titanium source; (2) The lithium iron phosphate is added to a mixture of a connector and a secondary carbon source for secondary mixing, followed by drying, secondary sintering, and crushing to obtain a lithium iron phosphate material.
2. The method for preparing the lithium iron phosphate material according to claim 1, characterized in that: The precursors with different titanium content include at least two of a first precursor, a second precursor, and a third precursor, wherein the content of the different titanium elements ranges from 500ppm to 3500ppm.
3. The method for preparing the lithium iron phosphate material according to claim 2, characterized in that: The titanium content of the first precursor is [500ppm, 1500ppm]; the titanium content of the second precursor is [1500ppm, 2500ppm]; the titanium content of the third precursor is (2500ppm, 3500ppm].
4. The method for preparing the lithium iron phosphate material according to claim 3, characterized in that: The precursors with different titanium content include any two of the first precursor, the second precursor and the third precursor.
5. The method for preparing the lithium iron phosphate material according to claim 3, characterized in that: The precursors with different titanium content include the first precursor, the second precursor and the third precursor.
6. The method for preparing the lithium iron phosphate material according to claim 4, characterized in that: The mass ratio of the first precursor and the second precursor, or the first precursor and the third precursor, or the second precursor and the third precursor is [10%, 50%]: [50%, 90%]; Preferably, the mass ratio of the first precursor and the second precursor, or the first precursor and the third precursor, or the second precursor and the third precursor is [20%, 40%]: [60%, 80%].
7. The method for preparing the lithium iron phosphate material according to claim 5, characterized in that: The mass ratio of the first precursor, the second precursor and the third precursor is (0%, 30%]: [50%, 90%]: (0%, 30%]; Preferably, the mass ratio of the first precursor, the second precursor and the third precursor is [5%, 15%]: [70%, 80%]: [5%, 15%].
8. The method for preparing lithium iron phosphate material according to claim 1, characterized in that: The connecting agent is a titanate coupling agent; and / or the secondary carbon source is a hydroxyl-containing carbon source.
9. The method for preparing the lithium iron phosphate material according to any one of claims 1 to 8, characterized in that: The mass ratio of the linker to the secondary carbon source is 1:[1,3]; And / or, the mass ratio of the connector to the lithium iron phosphate is 1:[80,100].
10. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material is prepared by the preparation method of the lithium iron phosphate material according to any one of claims 1 to 9, and the compaction density of the lithium iron phosphate material powder is [2.58g / cm 3 ,2.72 g / cm 3 ].
Citation Information
Patent Citations
Preparation method of high-compaction lithium iron phosphate material and lithium iron phosphate material prepared by same
CN112875671A
Preparation method of titanium-doped lithium iron phosphate material
CN116395658A
Preparation method of high-compaction high-mass energy density lithium iron phosphate
CN117317154A
Modified positive electrode material and preparation method and application thereof
CN117878315A
Cited By
Method for doping iron phosphate with titanium
CN120172374A
High-compaction and high-capacity lithium iron phosphate material as well as preparation method and application thereof
CN120208182A
A high-density, high-capacity lithium iron phosphate material and its preparation method and application
CN120208182B
Low-impurity phosphate positive electrode material and preparation method thereof, positive electrode and lithium secondary battery
CN120504306A
High-compaction and high-capacity lithium iron phosphate material, and preparation method therefor and use thereof
WO2026194202A1
